Regeneration Mechanism of Full Thickness Cartilage Defect Using Combination of Freeze Dried Bovine Cartilage Scaffold - Allogenic Bone Marrow Mesenchymal Stem Cells - Platelet Rich Plasma Composite (SMPC) Implantation - Ferdiansyah, Ferdiansyah; Utomo, Dwikora Novembri; Abdul Rantam, Fedik; Purwati, Purwati (Journal of biomimetics, biomaterials and biomedical engineering, 2017)
Cartilage defect has become serious problem for orthopaedic surgeon and patients because of its difficult healing that might occur when articular cartilage damage never reach subchondral layer. In this study, we used combination of freeze dried bovine cartilage (FDBC) scaffold, bone marrow mesenchymal stem cells (BM-MSCs), and platelet rich plasma (PRP) composite (SMPC) implanted in full thickness cartilage defect. This study is to explain its regeneration mechanism. This is true experimental research with post-test only control group design using New Zealand White Rabbit. 50 rabbits is divided into three groups of SMPC, BM-MSCs and FDBC. 37 rabbits evaluated after twelve weeks. Histopathologic examination showed the number of chondrocytes, collagen thickness and cartilage width are highest on SMPC group. Immunohistochemical examination showed SMPC group has the highest number of chondroprogenitor cells express FGF-2R, Sox-9, and MAPK. Brown Forsythe test resulted in significant increase the number of chondrocytes (p=0,010), collagen thickness (p=0,000), and cartilage surface width (p=0,015), and increase FGF-2R (p=0,000), MAPK (p=0,000), and Sox-9 (p=0,000) on SMPC group. Using path analysis, there is strong influence from FGF-2R, MAPK, and Sox-9 to the increase of chondrocytes, collagen thickness, and cartilage surface width. Hence, SMPC implantation mechanism of full thickness cartilage defect regeneration can be explained.